Prediction and Determination of Undrained Shear Strength of Soft Clay at Bukit Raja - Mohd Amin, Jamal; Taha, Mohd Raihan; Ahmed, Jimjali; Abu Kassim, Azmi; Jamaludin, Azmi; Jaadil, Jamilah (Universiti Putra Malaysia Press, 1997)
This paper presents the results of a study to predict and determine undrained shear strength, s", a very important parameter in design practice, for Klang clay, Malaysia. s is determined using field and laboratory vane shear and recompression method utilizing the direct simple shear (DSS) apparatus. Prediction of "was accomplished using the SHANSEP procedure and the critical state model. A test borehole at Bukit Raja, Klangs, was used for this study. Comparisons of s" values obtained by these methods are made. It is found that all the methods employed show the same trend of s" with depth. The vane shear test gives the highest estimation of s", followed by the recompression method, SHANSEP method and critical state method.